Legal Analysis of the Handling of M-Bangking Electronic Evidence in Bribery Cases in the Digital Era - Sagala, Sudarsono; Esther, July; Sinaga, Jusnizar (Indonesian Journal of Law and Justice, 2025)
Evidence in cybercrime cases can be easily erased or eliminated, and there are challenges in detecting crimes that occur in the banking sector that utilizes computer technology. This difficulty arises due to the lack of adequate equipment, the lack of courage of some victims to report the incident to the authorities, as well as the relatively weak security system of the owner of the asset or system. In addition, the difficulty in tracking the whereabouts of the perpetrators is also a significant problem. This research aims to examine and analyze how electronic evidence derived from M-banking transactions can be used in the process of proving bribery cases, as well as the challenges faced in law enforcement in Indonesia. The research method used is a normative approach with qualitative analysis, which includes literature studies and analysis of relevant regulations, such as the Electronic Information and Transaction Act (UU ITE) and the Code of Criminal Procedure (KUHAP). In this research, it was found that although the ITE Law gives recognition to electronic documents as valid evidence, there are obstacles in its application in court. The Criminal Code has not expressly regulated the recognition of electronic documents, which causes confusion in legal practice. In addition, technical challenges and lack of understanding among law enforcement officers regarding how to handle electronic evidence are also obstacles in the proof process.